A rapid, instrument-free, sample-to-result nucleic acid amplification test. Issue 19 (23rd August 2016) - Lafleur, Lisa K.; Bishop, Joshua D.; Heiniger, Erin K.; Gallagher, Ryan P.; Wheeler, Maxwell D.; Kauffman, Peter; Zhang, Xiaohong; Kline, Enos C.; Buser, Joshua R.; Kumar, Sujatha; Byrnes, Samantha A.; Vermeulen, Nicolaas M. J.; et al.
Abstract : This diagnostic system prototype is the first demonstration of a fully integrated, simple-to-use nucleic acid amplification test device. Abstract : The prototype demonstrated here is the first fully integrated sample-to-result diagnostic platform for performing nucleic acid amplification tests that requires no permanent instrument or manual sample processing. The multiplexable autonomous disposable nucleic acid amplification test (MAD NAAT) is based on two-dimensional paper networks, which enable sensitive chemical detection normally reserved for laboratories to be carried out anywhere by untrained users. All reagents are stored dry in the disposable test device and are rehydrated by stored buffer. The paper network is physically multiplexed to allow independent isothermal amplification of multiple targets; each amplification reaction is also chemically multiplexed with an internal amplification control. The total test time is less than one hour. The MAD NAAT prototype was used to characterize a set of human nasal swab specimens pre-screened for methicillin-resistant Staphylococcus aureus (MRSA) bacteria. With qPCR as the quantitative reference method, the lowest input copy number in the range where the MAD NAAT prototype consistently detected MRSA in these specimens was ∼5 × 10 3 genomic copies (∼600 genomic copies per biplexed amplification reaction).